Molecular Authentication of Meats from Three Terrestrial Birds Based on Pcr-Rflp Analysis of the Mitochondrial 12S rRNA Gene - H He; Y Wang; Y Qing; D Li; X Zhao; Q Zhu; H Yin (Brazilian Journal of Poultry Science)
ABSTRACT In this study, a method utilizing PCR-restriction fragment length polymorphism (PCR-RFLP) of a mitochondrial gene was developed for the identification of chicken (Gallus gallus), quail (Coturnix coturnix), and common pigeon (Columba livia) meat. PCR products of ~440 bp were obtained from the 12S rRNA gene of these three birds using a pair of universal primers. The three terrestrial birds can be distinguished using one restriction endonuclease, Alu I, which was selected based on species-specific variations in the mt 12S rRNA gene sequence using 9 newly-obtained and 44 published chicken, quail and pigeon sequences. This method was also successfully used to identify commercial quail and pigeon meat products, which were found to be adulterated with chicken meat. Additionally, our method had relatively high sensitivity for detecting a meat mixture. Ten percent of chicken meat in the mixed quail and pigeon sample was detectable. This assay can be useful for the accurate identification of meats from terrestrial birds, avoiding mislabeling or fraudulent species substitution in meat products.